Validation of an Area-Wide Extension Program to Estimate the Seasonal Abundance of Adult Citrus Root Weevils with Unbaited Pyramidal Traps - Stephen H. Futch; Larry W. Duncan; Mongi Zekri (EDIS)
This document is HS994, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2005. This research was supported by the Florida Agricultural Experiment Station, and approved for publication as Journal Series No. N-02573. This project is supported by the USDA Diaprepes Grant #727384112.